PELAKSANAAN FUNGSI UNIT PELAKSANA TEKNIS PERLINDUNGAN PEREMPUAN DAN PEREMPUAN (UPT PPA) TERKAIT PENCULIKAN DAN PERDAGANGAN ANAK DI KOTA PEKANBARU TAHUN 2021-2022 - Kurniawan, Ridho; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Kidnapping and child trafficking are forms of violence against children that cause physical and psychological suffering and deprive children of their freedom. The kidnapping and trafficking of children in the city of Pekanbaru increased from 3 cases in 2021 to 5 cases in 2022. There is a need for the implementation of good governance functions, if the government can carry out it’s functions effectively, then services will naturally yield justice, empowerment will foster independence, development will create prosperity, and regulation will establish conditions conductive to ongoing activities, including the creation of a good social order in community life. The handling of child abduction and trafficking is carried out by the Women’s empowerment, Child Protection, and Community Empowerment Office of Pekanbaru City and the Technical Implementation Unit for Women’s and Children’s Protection as the technical implementing element of DP3APM. The purpose of this research is to understand the implementation of the functions of the Technical Impelementation Unit for Women’s and Children’s Protection (UPT PPA) in addressing issues related to child abduction and trafficking in Pekanbaru City in 2021-2022. This research uses the Government Function theory by Ryaas Rasyid, which includes the functions of service, development, empowerment, and regulation. The research method is descriptive research with a qualitative approach. The data sources used are primary and secondary data. The data collection techniques are through interviews and documentation. The results of this research indicate that the UPT PPA of Pekanbaru City is capable of performing its service functions, as evidenced by the optimal management of kidnapping and trafficking cases. However, there are still shortcomings in facilities and infrastructure. In terms of development functions, the agency is building mobile units that can provide access to consultations, services, education, and also enhance the capacity of human resources through technical guidance. The empowerment function is carried out by establishing community- based PATBM activities, as well as conducting socialization and education. Furthermore, the regulatory function is executed by issuing Decree Number 239 of 2023. Keywords: UPT PPA, functions of government, kidnapping and child trafficking